Effect of Drought Stress and Osmopriming on the Growth and Yield of Tadong Upland Rice in Sabah, Malaysia - Robin Ah Hee Lim,; Evelyn Shin Rou Koay,; Mok Sam Lum, (Tropical Life Sciences Research, 2026)
Drought stress remains one of the most significant challenges facing the development and production of upland rice. Seed osmopriming represents a method to enhance plant growth and offers potential against drought stress. This study aimed to investigate the effects of polyethylene glycol (PEG) 6000 seed osmopriming and drought stress on the growth, yield, physiological and biochemical parameters of Tadong upland rice. The growth and yield of the Tadong upland rice variety were evaluated at five osmotic potentials using PEG 6000 for drought-induced osmopriming and at varying levels of drought stress with three soil moisture contents (SMC). Significant interaction effects between PEG 6000 osmotic potential levels and drought stress levels were observed across all measured parameters of Tadong upland rice. The combination of 20% SMC with -4 bar PEG proved optimal for growth and yield, showing a 55.68% increase compared to 10% SMC with -2 bar PEG, which produced the lowest yield per plant. Additional research should examine the effects of different PEG 6000 osmotic potential and drought stress levels on other upland rice varieties.